(untitled) (Bulletin of the International Association for Paleodontology, 2024)
To estimate the age at death of archaeological individuals through a radiographic analysis of the pulp/tooth area ratio in canines, according to Cameriere et al. (2007)’s method and its corresponding version adapted and validated for the contemporary Brazilian population. Sixty canines recovered from 30 individuals in five pre-colonial archaeological sites (Buracão, Piaçaguera, Tenório, Moraes, and Capelinha) in the state of São Paulo, Brazil, were examined. The specimens are under the custody of the Museum of Archeology and Ethnology at the University of São Paulo (MAE-USP). Pulp and tooth radiographic areas were measured by two calibrated examiners in the free software ImageJ®. The data ​​were applied to formulas to obtain age estimates. The intraclass correlation coefficient (ICC, p≤0.05) was calculated to analyze intra- and inter-examiner agreement. The estimates were compared against those previously cataloged by the MAE-USP using other anthropological methods. There was a significant intra-examiner (ICC = 0.888 to 0.99) and inter-examiner (ICC = 0.842 to 0.908) reproducibility regarding the estimated ages. Our data indicated that the age estimates obtained through the analysis of pulp/dental area ratio were similar to, or greater than, those previously determined by techniques commonly used in bioarchaeology. The method described herein can be accurately applied to individuals from a Brazilian archaeological collection, with the possibility of estimating their age based on the examination of a single tooth. Yet, this method should be ideally combined with other techniques and further studies should be performed with individuals from different archaeological populations.